Epigenetic-based targeted therapies for well-differentiated pancreatic neuroendocrine tumors: recent advances and future perspectives. Issue 6 (2nd November 2021) - Marini, Francesca; Giusti, Francesca; Brandi, Maria Luisa
ABSTRACT: Introduction: Well-differentiated pancreatic neuroendocrine tumors (PanNETs) are a heterogeneous group of primary tumors of the endocrine pancreas. Dysregulation of chromatin remodeling, gene expression alteration, global DNA hypomethylation of non-coding regions, DNA hypermethylation and silencing of tumor suppressor gene promoters are frequent epigenetic changes in PanNETs. These changes exert a role in neoplastic transformation and progression. As epigenetic mechanisms, converse to genetic mutations, are potentially reversible, they are an interesting and promising therapeutic target for the treatment of PanNETs. Areas covered: We reviewed main epigenetic alterations associated with the development, biological and clinical features and progression of PanNETs, as well as emerging therapies targeting epigenetic changes, which may prove effective for the treatment of human PanNETs. Expert opinion: Constant advances in the PanNET medical approach, as reported in the clinical and therapeutic recommendations of ESMO, improved the overall survival of patients over the years. However, over 60% of the patients with metastatic disease still have poor prognosis. Epigenetic regulator drugs, currently approved to treat some human malignancies, that showed anti-tumoral activity also on PanNETs, in pre-clinical and clinical studies, could concur to ameliorate the prognosis and OS of advanced and metastatic PanNET, in combination with surgery and currently employed medical therapies.